Elementary Functions - 4.35 Identities

From testwiki
Revision as of 11:09, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
4.35.E1 sinh ( u + v ) = sinh u cosh v + cosh u sinh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\sinh\left(u+v\right)=\sinh u\cosh v+\cosh u\sinh v}}
\sinh@{u+ v} = \sinh@@{u}\cosh@@{v}+\cosh@@{u}\sinh@@{v}

sinh(u + v) = sinh(u)*cosh(v)+ cosh(u)*sinh(v)
Sinh[u + v] == Sinh[u]*Cosh[v]+ Cosh[u]*Sinh[v]
Successful Successful - Successful [Tested: 100]
4.35.E1 sinh ( u - v ) = sinh u cosh v - cosh u sinh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\sinh\left(u-v\right)=\sinh u\cosh v-\cosh u\sinh v}}
\sinh@{u- v} = \sinh@@{u}\cosh@@{v}-\cosh@@{u}\sinh@@{v}

sinh(u - v) = sinh(u)*cosh(v)- cosh(u)*sinh(v)
Sinh[u - v] == Sinh[u]*Cosh[v]- Cosh[u]*Sinh[v]
Successful Successful - Successful [Tested: 100]
4.35.E2 cosh ( u + v ) = cosh u cosh v + sinh u sinh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\cosh\left(u+v\right)=\cosh u\cosh v+\sinh u\sinh v}}
\cosh@{u+ v} = \cosh@@{u}\cosh@@{v}+\sinh@@{u}\sinh@@{v}

cosh(u + v) = cosh(u)*cosh(v)+ sinh(u)*sinh(v)
Cosh[u + v] == Cosh[u]*Cosh[v]+ Sinh[u]*Sinh[v]
Successful Successful - Successful [Tested: 100]
4.35.E2 cosh ( u - v ) = cosh u cosh v - sinh u sinh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\cosh\left(u-v\right)=\cosh u\cosh v-\sinh u\sinh v}}
\cosh@{u- v} = \cosh@@{u}\cosh@@{v}-\sinh@@{u}\sinh@@{v}

cosh(u - v) = cosh(u)*cosh(v)- sinh(u)*sinh(v)
Cosh[u - v] == Cosh[u]*Cosh[v]- Sinh[u]*Sinh[v]
Successful Successful - Successful [Tested: 100]
4.35.E3 tanh ( u + v ) = tanh u + tanh v 1 + tanh u tanh v 𝑢 𝑣 𝑢 𝑣 1 𝑢 𝑣 {\displaystyle{\displaystyle\tanh\left(u+v\right)=\frac{\tanh u+\tanh v}{1+% \tanh u\tanh v}}}
\tanh@{u+ v} = \frac{\tanh@@{u}+\tanh@@{v}}{1+\tanh@@{u}\tanh@@{v}}

tanh(u + v) = (tanh(u)+ tanh(v))/(1 + tanh(u)*tanh(v))
Tanh[u + v] == Divide[Tanh[u]+ Tanh[v],1 + Tanh[u]*Tanh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E3 tanh ( u - v ) = tanh u - tanh v 1 - tanh u tanh v 𝑢 𝑣 𝑢 𝑣 1 𝑢 𝑣 {\displaystyle{\displaystyle\tanh\left(u-v\right)=\frac{\tanh u-\tanh v}{1-% \tanh u\tanh v}}}
\tanh@{u- v} = \frac{\tanh@@{u}-\tanh@@{v}}{1-\tanh@@{u}\tanh@@{v}}

tanh(u - v) = (tanh(u)- tanh(v))/(1 - tanh(u)*tanh(v))
Tanh[u - v] == Divide[Tanh[u]- Tanh[v],1 - Tanh[u]*Tanh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E4 coth ( u + v ) = + coth u coth v + 1 coth u + coth v hyperbolic-cotangent 𝑢 𝑣 hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 1 hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 {\displaystyle{\displaystyle\coth\left(u+v\right)=\frac{+\coth u\coth v+1}{% \coth u+\coth v}}}
\coth@{u+ v} = \frac{+\coth@@{u}\coth@@{v}+1}{\coth@@{u}+\coth@@{v}}

coth(u + v) = (+ coth(u)*coth(v)+ 1)/(coth(u)+ coth(v))
Coth[u + v] == Divide[+ Coth[u]*Coth[v]+ 1,Coth[u]+ Coth[v]]
Successful Successful -
Failed [10 / 100]
Result: Indeterminate
Test Values: {Rule[u, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[v, Power[E, Times[Complex[0, Rational[-5, 6]], Pi]]]}

Result: Complex[4.333014420201075*^14, -2.3525621062227262*^14]
Test Values: {Rule[u, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]], Rule[v, Power[E, Times[Complex[0, Rational[-1, 3]], Pi]]]}

... skip entries to safe data
4.35.E4 coth ( u - v ) = - coth u coth v + 1 coth u - coth v hyperbolic-cotangent 𝑢 𝑣 hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 1 hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 {\displaystyle{\displaystyle\coth\left(u-v\right)=\frac{-\coth u\coth v+1}{% \coth u-\coth v}}}
\coth@{u- v} = \frac{-\coth@@{u}\coth@@{v}+1}{\coth@@{u}-\coth@@{v}}

coth(u - v) = (- coth(u)*coth(v)+ 1)/(coth(u)- coth(v))
Coth[u - v] == Divide[- Coth[u]*Coth[v]+ 1,Coth[u]- Coth[v]]
Successful Successful -
Failed [10 / 100]
Result: Indeterminate
Test Values: {Rule[u, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[v, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Indeterminate
Test Values: {Rule[u, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]], Rule[v, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
4.35.E5 sinh u + sinh v = 2 sinh ( u + v 2 ) cosh ( u - v 2 ) 𝑢 𝑣 2 𝑢 𝑣 2 𝑢 𝑣 2 {\displaystyle{\displaystyle\sinh u+\sinh v=2\sinh\left(\frac{u+v}{2}\right)% \cosh\left(\frac{u-v}{2}\right)}}
\sinh@@{u}+\sinh@@{v} = 2\sinh@{\frac{u+v}{2}}\cosh@{\frac{u-v}{2}}

sinh(u)+ sinh(v) = 2*sinh((u + v)/(2))*cosh((u - v)/(2))
Sinh[u]+ Sinh[v] == 2*Sinh[Divide[u + v,2]]*Cosh[Divide[u - v,2]]
Successful Successful - Successful [Tested: 100]
4.35.E6 sinh u - sinh v = 2 cosh ( u + v 2 ) sinh ( u - v 2 ) 𝑢 𝑣 2 𝑢 𝑣 2 𝑢 𝑣 2 {\displaystyle{\displaystyle\sinh u-\sinh v=2\cosh\left(\frac{u+v}{2}\right)% \sinh\left(\frac{u-v}{2}\right)}}
\sinh@@{u}-\sinh@@{v} = 2\cosh@{\frac{u+v}{2}}\sinh@{\frac{u-v}{2}}

sinh(u)- sinh(v) = 2*cosh((u + v)/(2))*sinh((u - v)/(2))
Sinh[u]- Sinh[v] == 2*Cosh[Divide[u + v,2]]*Sinh[Divide[u - v,2]]
Successful Successful - Successful [Tested: 100]
4.35.E7 cosh u + cosh v = 2 cosh ( u + v 2 ) cosh ( u - v 2 ) 𝑢 𝑣 2 𝑢 𝑣 2 𝑢 𝑣 2 {\displaystyle{\displaystyle\cosh u+\cosh v=2\cosh\left(\frac{u+v}{2}\right)% \cosh\left(\frac{u-v}{2}\right)}}
\cosh@@{u}+\cosh@@{v} = 2\cosh@{\frac{u+v}{2}}\cosh@{\frac{u-v}{2}}

cosh(u)+ cosh(v) = 2*cosh((u + v)/(2))*cosh((u - v)/(2))
Cosh[u]+ Cosh[v] == 2*Cosh[Divide[u + v,2]]*Cosh[Divide[u - v,2]]
Successful Successful - Successful [Tested: 100]
4.35.E8 cosh u - cosh v = 2 sinh ( u + v 2 ) sinh ( u - v 2 ) 𝑢 𝑣 2 𝑢 𝑣 2 𝑢 𝑣 2 {\displaystyle{\displaystyle\cosh u-\cosh v=2\sinh\left(\frac{u+v}{2}\right)% \sinh\left(\frac{u-v}{2}\right)}}
\cosh@@{u}-\cosh@@{v} = 2\sinh@{\frac{u+v}{2}}\sinh@{\frac{u-v}{2}}

cosh(u)- cosh(v) = 2*sinh((u + v)/(2))*sinh((u - v)/(2))
Cosh[u]- Cosh[v] == 2*Sinh[Divide[u + v,2]]*Sinh[Divide[u - v,2]]
Successful Successful - Successful [Tested: 100]
4.35.E9 tanh u + tanh v = sinh ( u + v ) cosh u cosh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\tanh u+\tanh v=\frac{\sinh\left(u+v\right)}{\cosh u% \cosh v}}}
\tanh@@{u}+\tanh@@{v} = \frac{\sinh@{u+ v}}{\cosh@@{u}\cosh@@{v}}

tanh(u)+ tanh(v) = (sinh(u + v))/(cosh(u)*cosh(v))
Tanh[u]+ Tanh[v] == Divide[Sinh[u + v],Cosh[u]*Cosh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E9 tanh u - tanh v = sinh ( u - v ) cosh u cosh v 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle\tanh u-\tanh v=\frac{\sinh\left(u-v\right)}{\cosh u% \cosh v}}}
\tanh@@{u}-\tanh@@{v} = \frac{\sinh@{u- v}}{\cosh@@{u}\cosh@@{v}}

tanh(u)- tanh(v) = (sinh(u - v))/(cosh(u)*cosh(v))
Tanh[u]- Tanh[v] == Divide[Sinh[u - v],Cosh[u]*Cosh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E10 coth u + coth v = sinh ( v + u ) sinh u sinh v hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 𝑣 𝑢 𝑢 𝑣 {\displaystyle{\displaystyle\coth u+\coth v=\frac{\sinh\left(v+u\right)}{\sinh u% \sinh v}}}
\coth@@{u}+\coth@@{v} = \frac{\sinh@{v+ u}}{\sinh@@{u}\sinh@@{v}}

coth(u)+ coth(v) = (sinh(v + u))/(sinh(u)*sinh(v))
Coth[u]+ Coth[v] == Divide[Sinh[v + u],Sinh[u]*Sinh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E10 coth u - coth v = sinh ( v - u ) sinh u sinh v hyperbolic-cotangent 𝑢 hyperbolic-cotangent 𝑣 𝑣 𝑢 𝑢 𝑣 {\displaystyle{\displaystyle\coth u-\coth v=\frac{\sinh\left(v-u\right)}{\sinh u% \sinh v}}}
\coth@@{u}-\coth@@{v} = \frac{\sinh@{v- u}}{\sinh@@{u}\sinh@@{v}}

coth(u)- coth(v) = (sinh(v - u))/(sinh(u)*sinh(v))
Coth[u]- Coth[v] == Divide[Sinh[v - u],Sinh[u]*Sinh[v]]
Successful Successful - Successful [Tested: 100]
4.35.E11 cosh 2 z - sinh 2 z = 1 2 𝑧 2 𝑧 1 {\displaystyle{\displaystyle{\cosh^{2}}z-{\sinh^{2}}z=1}}
\cosh^{2}@@{z}-\sinh^{2}@@{z} = 1

(cosh(z))^(2)- (sinh(z))^(2) = 1
(Cosh[z])^(2)- (Sinh[z])^(2) == 1
Successful Successful - Successful [Tested: 7]
4.35.E12 sech 2 z = 1 - tanh 2 z 2 𝑧 1 2 𝑧 {\displaystyle{\displaystyle{\operatorname{sech}^{2}}z=1-{\tanh^{2}}z}}
\sech^{2}@@{z} = 1-\tanh^{2}@@{z}

(sech(z))^(2) = 1 - (tanh(z))^(2)
(Sech[z])^(2) == 1 - (Tanh[z])^(2)
Successful Successful - Successful [Tested: 7]
4.35.E13 csch 2 z = coth 2 z - 1 2 𝑧 hyperbolic-cotangent 2 𝑧 1 {\displaystyle{\displaystyle{\operatorname{csch}^{2}}z={\coth^{2}}z-1}}
\csch^{2}@@{z} = \coth^{2}@@{z}-1

(csch(z))^(2) = (coth(z))^(2)- 1
(Csch[z])^(2) == (Coth[z])^(2)- 1
Successful Successful - Successful [Tested: 7]
4.35.E14 2 sinh u sinh v = cosh ( u + v ) - cosh ( u - v ) 2 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle 2\sinh u\sinh v=\cosh\left(u+v\right)-\cosh\left(% u-v\right)}}
2\sinh@@{u}\sinh@@{v} = \cosh@{u+v}-\cosh@{u-v}

2*sinh(u)*sinh(v) = cosh(u + v)- cosh(u - v)
2*Sinh[u]*Sinh[v] == Cosh[u + v]- Cosh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E15 2 cosh u cosh v = cosh ( u + v ) + cosh ( u - v ) 2 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle 2\cosh u\cosh v=\cosh\left(u+v\right)+\cosh\left(% u-v\right)}}
2\cosh@@{u}\cosh@@{v} = \cosh@{u+v}+\cosh@{u-v}

2*cosh(u)*cosh(v) = cosh(u + v)+ cosh(u - v)
2*Cosh[u]*Cosh[v] == Cosh[u + v]+ Cosh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E16 2 sinh u cosh v = sinh ( u + v ) + sinh ( u - v ) 2 𝑢 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle 2\sinh u\cosh v=\sinh\left(u+v\right)+\sinh\left(% u-v\right)}}
2\sinh@@{u}\cosh@@{v} = \sinh@{u+v}+\sinh@{u-v}

2*sinh(u)*cosh(v) = sinh(u + v)+ sinh(u - v)
2*Sinh[u]*Cosh[v] == Sinh[u + v]+ Sinh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E17 sinh 2 u - sinh 2 v = sinh ( u + v ) sinh ( u - v ) 2 𝑢 2 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle{\sinh^{2}}u-{\sinh^{2}}v=\sinh\left(u+v\right)% \sinh\left(u-v\right)}}
\sinh^{2}@@{u}-\sinh^{2}@@{v} = \sinh@{u+v}\sinh@{u-v}

(sinh(u))^(2)- (sinh(v))^(2) = sinh(u + v)*sinh(u - v)
(Sinh[u])^(2)- (Sinh[v])^(2) == Sinh[u + v]*Sinh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E18 cosh 2 u - cosh 2 v = sinh ( u + v ) sinh ( u - v ) 2 𝑢 2 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle{\cosh^{2}}u-{\cosh^{2}}v=\sinh\left(u+v\right)% \sinh\left(u-v\right)}}
\cosh^{2}@@{u}-\cosh^{2}@@{v} = \sinh@{u+v}\sinh@{u-v}

(cosh(u))^(2)- (cosh(v))^(2) = sinh(u + v)*sinh(u - v)
(Cosh[u])^(2)- (Cosh[v])^(2) == Sinh[u + v]*Sinh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E19 sinh 2 u + cosh 2 v = cosh ( u + v ) cosh ( u - v ) 2 𝑢 2 𝑣 𝑢 𝑣 𝑢 𝑣 {\displaystyle{\displaystyle{\sinh^{2}}u+{\cosh^{2}}v=\cosh\left(u+v\right)% \cosh\left(u-v\right)}}
\sinh^{2}@@{u}+\cosh^{2}@@{v} = \cosh@{u+v}\cosh@{u-v}

(sinh(u))^(2)+ (cosh(v))^(2) = cosh(u + v)*cosh(u - v)
(Sinh[u])^(2)+ (Cosh[v])^(2) == Cosh[u + v]*Cosh[u - v]
Successful Successful - Successful [Tested: 100]
4.35.E20 sinh z 2 = ( cosh z - 1 2 ) 1 / 2 𝑧 2 superscript 𝑧 1 2 1 2 {\displaystyle{\displaystyle\sinh\frac{z}{2}=\left(\frac{\cosh z-1}{2}\right)^% {1/2}}}
\sinh@@{\frac{z}{2}} = \left(\frac{\cosh@@{z}-1}{2}\right)^{1/2}

sinh((z)/(2)) = ((cosh(z)- 1)/(2))^(1/2)
Sinh[Divide[z,2]] == (Divide[Cosh[z]- 1,2])^(1/2)
Failure Failure
Failed [2 / 7]
Result: -.4585952894+.8655770340*I
Test Values: {z = -1/2+1/2*I*3^(1/2)}

Result: -.8655716642-.5419255224*I
Test Values: {z = -1/2*3^(1/2)-1/2*I}

Failed [2 / 7]
Result: Complex[-0.4585952893468803, 0.8655770337160631]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

Result: Complex[-0.8655716640572735, -0.5419255224573363]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[-5, 6]], Pi]]]}

4.35.E21 cosh z 2 = ( cosh z + 1 2 ) 1 / 2 𝑧 2 superscript 𝑧 1 2 1 2 {\displaystyle{\displaystyle\cosh\frac{z}{2}=\left(\frac{\cosh z+1}{2}\right)^% {1/2}}}
\cosh@@{\frac{z}{2}} = \left(\frac{\cosh@@{z}+1}{2}\right)^{1/2}

cosh((z)/(2)) = ((cosh(z)+ 1)/(2))^(1/2)
Cosh[Divide[z,2]] == (Divide[Cosh[z]+ 1,2])^(1/2)
Failure Failure Successful [Tested: 7] Successful [Tested: 7]
4.35.E22 tanh z 2 = ( cosh z - 1 cosh z + 1 ) 1 / 2 𝑧 2 superscript 𝑧 1 𝑧 1 1 2 {\displaystyle{\displaystyle\tanh\frac{z}{2}=\left(\frac{\cosh z-1}{\cosh z+1}% \right)^{1/2}}}
\tanh@@{\frac{z}{2}} = \left(\frac{\cosh@@{z}-1}{\cosh@@{z}+1}\right)^{1/2}

tanh((z)/(2)) = ((cosh(z)- 1)/(cosh(z)+ 1))^(1/2)
Tanh[Divide[z,2]] == (Divide[Cosh[z]- 1,Cosh[z]+ 1])^(1/2)
Failure Failure
Failed [2 / 7]
Result: -.5869891489+.8580864930*I
Test Values: {z = -1/2+1/2*I*3^(1/2)}

Result: -.8595320616-.4211742148*I
Test Values: {z = -1/2*3^(1/2)-1/2*I}

Failed [2 / 7]
Result: Complex[-0.5869891488727425, 0.858086492859854]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

Result: Complex[-0.8595320613685857, -0.42117421488499707]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[-5, 6]], Pi]]]}

4.35.E22 ( cosh z - 1 cosh z + 1 ) 1 / 2 = cosh z - 1 sinh z superscript 𝑧 1 𝑧 1 1 2 𝑧 1 𝑧 {\displaystyle{\displaystyle\left(\frac{\cosh z-1}{\cosh z+1}\right)^{1/2}=% \frac{\cosh z-1}{\sinh z}}}
\left(\frac{\cosh@@{z}-1}{\cosh@@{z}+1}\right)^{1/2} = \frac{\cosh@@{z}-1}{\sinh@@{z}}

((cosh(z)- 1)/(cosh(z)+ 1))^(1/2) = (cosh(z)- 1)/(sinh(z))
(Divide[Cosh[z]- 1,Cosh[z]+ 1])^(1/2) == Divide[Cosh[z]- 1,Sinh[z]]
Failure Failure
Failed [2 / 7]
Result: .5869891489-.8580864930*I
Test Values: {z = -1/2+1/2*I*3^(1/2)}

Result: .8595320615+.4211742148*I
Test Values: {z = -1/2*3^(1/2)-1/2*I}

Failed [2 / 7]
Result: Complex[0.5869891488727426, -0.8580864928598539]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

Result: Complex[0.859532061368586, 0.42117421488499684]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[-5, 6]], Pi]]]}

4.35.E22 cosh z - 1 sinh z = sinh z cosh z + 1 𝑧 1 𝑧 𝑧 𝑧 1 {\displaystyle{\displaystyle\frac{\cosh z-1}{\sinh z}=\frac{\sinh z}{\cosh z+1% }}}
\frac{\cosh@@{z}-1}{\sinh@@{z}} = \frac{\sinh@@{z}}{\cosh@@{z}+1}

(cosh(z)- 1)/(sinh(z)) = (sinh(z))/(cosh(z)+ 1)
Divide[Cosh[z]- 1,Sinh[z]] == Divide[Sinh[z],Cosh[z]+ 1]
Successful Successful Skip - symbolical successful subtest Successful [Tested: 7]
4.35.E23 sinh ( - z ) = - sinh z 𝑧 𝑧 {\displaystyle{\displaystyle\sinh\left(-z\right)=-\sinh z}}
\sinh@{-z} = -\sinh@@{z}

sinh(- z) = - sinh(z)
Sinh[- z] == - Sinh[z]
Successful Successful - Successful [Tested: 7]
4.35.E24 cosh ( - z ) = cosh z 𝑧 𝑧 {\displaystyle{\displaystyle\cosh\left(-z\right)=\cosh z}}
\cosh@{-z} = \cosh@@{z}

cosh(- z) = cosh(z)
Cosh[- z] == Cosh[z]
Successful Successful - Successful [Tested: 7]
4.35.E25 tanh ( - z ) = - tanh z 𝑧 𝑧 {\displaystyle{\displaystyle\tanh\left(-z\right)=-\tanh z}}
\tanh@{-z} = -\tanh@@{z}

tanh(- z) = - tanh(z)
Tanh[- z] == - Tanh[z]
Successful Successful - Successful [Tested: 7]
4.35.E26 sinh ( 2 z ) = 2 sinh z cosh z 2 𝑧 2 𝑧 𝑧 {\displaystyle{\displaystyle\sinh\left(2z\right)=2\sinh z\cosh z}}
\sinh@{2z} = 2\sinh@@{z}\cosh@@{z}

sinh(2*z) = 2*sinh(z)*cosh(z)
Sinh[2*z] == 2*Sinh[z]*Cosh[z]
Successful Successful - Successful [Tested: 7]
4.35.E26 2 sinh z cosh z = 2 tanh z 1 - tanh 2 z 2 𝑧 𝑧 2 𝑧 1 2 𝑧 {\displaystyle{\displaystyle 2\sinh z\cosh z=\frac{2\tanh z}{1-{\tanh^{2}}z}}}
2\sinh@@{z}\cosh@@{z} = \frac{2\tanh@@{z}}{1-\tanh^{2}@@{z}}

2*sinh(z)*cosh(z) = (2*tanh(z))/(1 - (tanh(z))^(2))
2*Sinh[z]*Cosh[z] == Divide[2*Tanh[z],1 - (Tanh[z])^(2)]
Successful Successful - Successful [Tested: 7]
4.35.E27 cosh ( 2 z ) = 2 cosh 2 z - 1 2 𝑧 2 2 𝑧 1 {\displaystyle{\displaystyle\cosh\left(2z\right)=2{\cosh^{2}}z-1}}
\cosh@{2z} = 2\cosh^{2}@@{z}-1

cosh(2*z) = 2*(cosh(z))^(2)- 1
Cosh[2*z] == 2*(Cosh[z])^(2)- 1
Successful Successful - Successful [Tested: 7]
4.35.E27 2 cosh 2 z - 1 = 2 sinh 2 z + 1 2 2 𝑧 1 2 2 𝑧 1 {\displaystyle{\displaystyle 2{\cosh^{2}}z-1=2{\sinh^{2}}z+1\\ }}
2\cosh^{2}@@{z}-1 = 2\sinh^{2}@@{z}+1\\

2*(cosh(z))^(2)- 1 = 2*(sinh(z))^(2)+ 1
2*(Cosh[z])^(2)- 1 == 2*(Sinh[z])^(2)+ 1
Successful Successful - Successful [Tested: 7]
4.35.E27 2 sinh 2 z + 1 = cosh 2 z + sinh 2 z 2 2 𝑧 1 2 𝑧 2 𝑧 {\displaystyle{\displaystyle 2{\sinh^{2}}z+1\\ ={\cosh^{2}}z+{\sinh^{2}}z}}
2\sinh^{2}@@{z}+1\\ = \cosh^{2}@@{z}+\sinh^{2}@@{z}

2*(sinh(z))^(2)+ 1 = (cosh(z))^(2)+ (sinh(z))^(2)
2*(Sinh[z])^(2)+ 1 == (Cosh[z])^(2)+ (Sinh[z])^(2)
Successful Successful - Successful [Tested: 7]
4.35.E28 tanh ( 2 z ) = 2 tanh z 1 + tanh 2 z 2 𝑧 2 𝑧 1 2 𝑧 {\displaystyle{\displaystyle\tanh\left(2z\right)=\frac{2\tanh z}{1+{\tanh^{2}}% z}}}
\tanh@{2z} = \frac{2\tanh@@{z}}{1+\tanh^{2}@@{z}}

tanh(2*z) = (2*tanh(z))/(1 + (tanh(z))^(2))
Tanh[2*z] == Divide[2*Tanh[z],1 + (Tanh[z])^(2)]
Successful Successful - Successful [Tested: 7]
4.35.E29 sinh ( 3 z ) = 3 sinh z + 4 sinh 3 z 3 𝑧 3 𝑧 4 3 𝑧 {\displaystyle{\displaystyle\sinh\left(3z\right)=3\sinh z+4{\sinh^{3}}z}}
\sinh@{3z} = 3\sinh@@{z}+4\sinh^{3}@@{z}

sinh(3*z) = 3*sinh(z)+ 4*(sinh(z))^(3)
Sinh[3*z] == 3*Sinh[z]+ 4*(Sinh[z])^(3)
Successful Successful - Successful [Tested: 7]
4.35.E30 cosh ( 3 z ) = - 3 cosh z + 4 cosh 3 z 3 𝑧 3 𝑧 4 3 𝑧 {\displaystyle{\displaystyle\cosh\left(3z\right)=-3\cosh z+4{\cosh^{3}}z}}
\cosh@{3z} = -3\cosh@@{z}+4\cosh^{3}@@{z}

cosh(3*z) = - 3*cosh(z)+ 4*(cosh(z))^(3)
Cosh[3*z] == - 3*Cosh[z]+ 4*(Cosh[z])^(3)
Successful Successful - Successful [Tested: 7]
4.35.E31 sinh ( 4 z ) = 4 sinh 3 z cosh z + 4 cosh 3 z sinh z 4 𝑧 4 3 𝑧 𝑧 4 3 𝑧 𝑧 {\displaystyle{\displaystyle\sinh\left(4z\right)=4{\sinh^{3}}z\cosh z+4{\cosh^% {3}}z\sinh z}}
\sinh@{4z} = 4\sinh^{3}@@{z}\cosh@@{z}+4\cosh^{3}@@{z}\sinh@@{z}

sinh(4*z) = 4*(sinh(z))^(3)* cosh(z)+ 4*(cosh(z))^(3)* sinh(z)
Sinh[4*z] == 4*(Sinh[z])^(3)* Cosh[z]+ 4*(Cosh[z])^(3)* Sinh[z]
Successful Successful - Successful [Tested: 7]
4.35.E32 cosh ( 4 z ) = cosh 4 z + 6 sinh 2 z cosh 2 z + sinh 4 z 4 𝑧 4 𝑧 6 2 𝑧 2 𝑧 4 𝑧 {\displaystyle{\displaystyle\cosh\left(4z\right)={\cosh^{4}}z+6{\sinh^{2}}z{% \cosh^{2}}z+{\sinh^{4}}z}}
\cosh@{4z} = \cosh^{4}@@{z}+6\sinh^{2}@@{z}\cosh^{2}@@{z}+\sinh^{4}@@{z}

cosh(4*z) = (cosh(z))^(4)+ 6*(sinh(z))^(2)* (cosh(z))^(2)+ (sinh(z))^(4)
Cosh[4*z] == (Cosh[z])^(4)+ 6*(Sinh[z])^(2)* (Cosh[z])^(2)+ (Sinh[z])^(4)
Successful Successful - Successful [Tested: 7]
4.35.E33 cosh ( n z ) + sinh ( n z ) = ( cosh z + sinh z ) n 𝑛 𝑧 𝑛 𝑧 superscript 𝑧 𝑧 𝑛 {\displaystyle{\displaystyle\cosh\left(nz\right)+\sinh\left(nz\right)=(\cosh z% +\sinh z)^{n}}}
\cosh@{nz}+\sinh@{nz} = (\cosh@@{z}+\sinh@@{z})^{n}

cosh(n*z)+ sinh(n*z) = (cosh(z)+ sinh(z))^(n)
Cosh[n*z]+ Sinh[n*z] == (Cosh[z]+ Sinh[z])^(n)
Successful Successful - Successful [Tested: 7]
4.35.E33 cosh ( n z ) - sinh ( n z ) = ( cosh z - sinh z ) n 𝑛 𝑧 𝑛 𝑧 superscript 𝑧 𝑧 𝑛 {\displaystyle{\displaystyle\cosh\left(nz\right)-\sinh\left(nz\right)=(\cosh z% -\sinh z)^{n}}}
\cosh@{nz}-\sinh@{nz} = (\cosh@@{z}-\sinh@@{z})^{n}

cosh(n*z)- sinh(n*z) = (cosh(z)- sinh(z))^(n)
Cosh[n*z]- Sinh[n*z] == (Cosh[z]- Sinh[z])^(n)
Successful Successful - Successful [Tested: 7]
4.35.E34 sinh z = sinh x cos y + i cosh x sin y 𝑧 𝑥 𝑦 𝑖 𝑥 𝑦 {\displaystyle{\displaystyle\sinh z=\sinh x\cos y+i\cosh x\sin y}}
\sinh@@{z} = \sinh@@{x}\cos@@{y}+i\cosh@@{x}\sin@@{y}

sinh(x + y*I) = sinh(x)*cos(y)+ I*cosh(x)*sin(y)
Sinh[x + y*I] == Sinh[x]*Cos[y]+ I*Cosh[x]*Sin[y]
Successful Successful - Successful [Tested: 18]
4.35.E35 cosh z = cosh x cos y + i sinh x sin y 𝑧 𝑥 𝑦 𝑖 𝑥 𝑦 {\displaystyle{\displaystyle\cosh z=\cosh x\cos y+i\sinh x\sin y}}
\cosh@@{z} = \cosh@@{x}\cos@@{y}+i\sinh@@{x}\sin@@{y}

cosh(x + y*I) = cosh(x)*cos(y)+ I*sinh(x)*sin(y)
Cosh[x + y*I] == Cosh[x]*Cos[y]+ I*Sinh[x]*Sin[y]
Successful Successful - Successful [Tested: 18]
4.35.E36 tanh z = sinh ( 2 x ) + i sin ( 2 y ) cosh ( 2 x ) + cos ( 2 y ) 𝑧 2 𝑥 𝑖 2 𝑦 2 𝑥 2 𝑦 {\displaystyle{\displaystyle\tanh z=\frac{\sinh\left(2x\right)+i\sin\left(2y% \right)}{\cosh\left(2x\right)+\cos\left(2y\right)}}}
\tanh@@{z} = \frac{\sinh@{2x}+i\sin@{2y}}{\cosh@{2x}+\cos@{2y}}

tanh(x + y*I) = (sinh(2*x)+ I*sin(2*y))/(cosh(2*x)+ cos(2*y))
Tanh[x + y*I] == Divide[Sinh[2*x]+ I*Sin[2*y],Cosh[2*x]+ Cos[2*y]]
Successful Successful - Successful [Tested: 18]
4.35.E37 coth z = sinh ( 2 x ) - i sin ( 2 y ) cosh ( 2 x ) - cos ( 2 y ) hyperbolic-cotangent 𝑧 2 𝑥 𝑖 2 𝑦 2 𝑥 2 𝑦 {\displaystyle{\displaystyle\coth z=\frac{\sinh\left(2x\right)-i\sin\left(2y% \right)}{\cosh\left(2x\right)-\cos\left(2y\right)}}}
\coth@@{z} = \frac{\sinh@{2x}-i\sin@{2y}}{\cosh@{2x}-\cos@{2y}}

coth(x + y*I) = (sinh(2*x)- I*sin(2*y))/(cosh(2*x)- cos(2*y))
Coth[x + y*I] == Divide[Sinh[2*x]- I*Sin[2*y],Cosh[2*x]- Cos[2*y]]
Successful Successful - Successful [Tested: 18]
4.35.E38 | sinh z | = ( sinh 2 x + sin 2 y ) 1 / 2 𝑧 superscript 2 𝑥 2 𝑦 1 2 {\displaystyle{\displaystyle|\sinh z|=({\sinh^{2}}x+{\sin^{2}}y)^{1/2}}}
|\sinh@@{z}| = (\sinh^{2}@@{x}+\sin^{2}@@{y})^{1/2}

abs(sinh(x + y*I)) = ((sinh(x))^(2)+ (sin(y))^(2))^(1/2)
Abs[Sinh[x + y*I]] == ((Sinh[x])^(2)+ (Sin[y])^(2))^(1/2)
Successful Failure - Successful [Tested: 18]
4.35.E38 ( sinh 2 x + sin 2 y ) 1 / 2 = ( 1 2 ( cosh ( 2 x ) - cos ( 2 y ) ) ) 1 / 2 superscript 2 𝑥 2 𝑦 1 2 superscript 1 2 2 𝑥 2 𝑦 1 2 {\displaystyle{\displaystyle({\sinh^{2}}x+{\sin^{2}}y)^{1/2}=\left(\tfrac{1}{2% }(\cosh\left(2x\right)-\cos\left(2y\right))\right)^{1/2}}}
(\sinh^{2}@@{x}+\sin^{2}@@{y})^{1/2} = \left(\tfrac{1}{2}(\cosh@{2x}-\cos@{2y})\right)^{1/2}

((sinh(x))^(2)+ (sin(y))^(2))^(1/2) = ((1)/(2)*(cosh(2*x)- cos(2*y)))^(1/2)
((Sinh[x])^(2)+ (Sin[y])^(2))^(1/2) == (Divide[1,2]*(Cosh[2*x]- Cos[2*y]))^(1/2)
Successful Successful - Successful [Tested: 18]
4.35.E39 | cosh z | = ( sinh 2 x + cos 2 y ) 1 / 2 𝑧 superscript 2 𝑥 2 𝑦 1 2 {\displaystyle{\displaystyle|\cosh z|=({\sinh^{2}}x+{\cos^{2}}y)^{1/2}}}
|\cosh@@{z}| = (\sinh^{2}@@{x}+\cos^{2}@@{y})^{1/2}

abs(cosh(x + y*I)) = ((sinh(x))^(2)+ (cos(y))^(2))^(1/2)
Abs[Cosh[x + y*I]] == ((Sinh[x])^(2)+ (Cos[y])^(2))^(1/2)
Successful Failure - Successful [Tested: 18]
4.35.E39 ( sinh 2 x + cos 2 y ) 1 / 2 = ( 1 2 ( cosh ( 2 x ) + cos ( 2 y ) ) ) 1 / 2 superscript 2 𝑥 2 𝑦 1 2 superscript 1 2 2 𝑥 2 𝑦 1 2 {\displaystyle{\displaystyle({\sinh^{2}}x+{\cos^{2}}y)^{1/2}=\left(\tfrac{1}{2% }(\cosh\left(2x\right)+\cos\left(2y\right))\right)^{1/2}}}
(\sinh^{2}@@{x}+\cos^{2}@@{y})^{1/2} = \left(\tfrac{1}{2}(\cosh@{2x}+\cos@{2y})\right)^{1/2}

((sinh(x))^(2)+ (cos(y))^(2))^(1/2) = ((1)/(2)*(cosh(2*x)+ cos(2*y)))^(1/2)
((Sinh[x])^(2)+ (Cos[y])^(2))^(1/2) == (Divide[1,2]*(Cosh[2*x]+ Cos[2*y]))^(1/2)
Successful Successful - Successful [Tested: 18]
4.35.E40 | tanh z | = ( cosh ( 2 x ) - cos ( 2 y ) cosh ( 2 x ) + cos ( 2 y ) ) 1 / 2 𝑧 superscript 2 𝑥 2 𝑦 2 𝑥 2 𝑦 1 2 {\displaystyle{\displaystyle|\tanh z|=\left(\frac{\cosh\left(2x\right)-\cos% \left(2y\right)}{\cosh\left(2x\right)+\cos\left(2y\right)}\right)^{1/2}}}
|\tanh@@{z}| = \left(\frac{\cosh@{2x}-\cos@{2y}}{\cosh@{2x}+\cos@{2y}}\right)^{1/2}

abs(tanh(x + y*I)) = ((cosh(2*x)- cos(2*y))/(cosh(2*x)+ cos(2*y)))^(1/2)
Abs[Tanh[x + y*I]] == (Divide[Cosh[2*x]- Cos[2*y],Cosh[2*x]+ Cos[2*y]])^(1/2)
Successful Failure - Successful [Tested: 18]